The Influence of Principal Leadership, Work Motivation, and School Culture on Teacher Performance at SMK Nasional Malang - Azizah, Habib Nun; Imron, Ali; Kusumaningrum, Desi Era; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
This study examines the influence of principal leadership, work motivation, and school culture on teacher performance at SMK Nasional Malang. Using literature review and observation methods, this research analyzes data from various sources and the researchers’ direct experiences during the MBKM program. The results show that the principal’s transformational leadership significantly affects teacher performance. An inclusive school culture, including routine activities such as morning greetings, joint prayers, and congregational prayers, contributes to the formation of discipline and character. Policies such as the moving class system enhance teacher motivation. Collaboration among school members strengthens the sense of togetherness and creates a conducive working environment. The combination of effective leadership, high motivation, and a positive school culture has been proven to improve teacher performance, which in turn promotes the quality of education at SMK Nasional Malang.